Peran Sumber Daya Manusia dalam Mengelola Sumber Daya Alam untuk Mendukung Pertumbuhan Ekonomi - Evi Novita Sari; Nikmatul Khofifah; Azizatun Niswah; Nurus Sobakh (Indo Publishing, 2026)
Human resources play a crucial role in managing natural resources to support sustainable economic growth. The increasing exploitation of natural resources without proper management has led to environmental degradation and reduced long-term economic benefits. Therefore, the presence of competent, skilled, and responsible human resources is essential to ensure that natural resource management is conducted efficiently and sustainably. This study aims to analyze the role of human resources in managing natural resources and their impact on economic growth. The method used is a qualitative approach through literature review by examining various relevant scientific sources. The results indicate that human resources contribute significantly through innovation, technology utilization, environmental awareness, and policy implementation in natural resource management. Effective human resource management can enhance productivity, maintain environmental balance, and create sustainable economic value. In conclusion, the quality of human resources is a key factor in optimizing natural resource management to achieve stable and sustainable economic growth.